2011
DOI: 10.1186/1471-2377-11-147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cognitive impairment in individuals aged over 65 in an urban area: DERIVA study

Abstract: BackgroundFew data are available on the prevalence of cognitive impairment (CI) in Spain, and the existing information shows important variations depending on the geographical setting and the methodology employed. The aim of this study was to determine the prevalence of CI in individuals aged over 65 in an urban area, and to analyze its associated risk factors.MethodsDesign: A descriptive, cross-sectional, home questionnaire-based study; Setting: Populational, urban setting. Participants: The reference populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
41
1
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 44 publications
21
41
1
12
Order By: Relevance
“…The superior schooling of Chilean women, as well as their prolonged interactions with family members, might stimulate cognitive function (28,29) . As in other studies, a lower risk of cognitive impairment was observed in those with higher levels of education (30)(31)(32) , which might be explained by greater cognitive reserves from superior cortical and neuronal synaptic capacities or improved compensation for deficiencies arising from other brain regions (33,34) . Although the difference in SF levels was statistically significant when comparing our participants with normal and impaired cognitive function (MMMSE plus PFAQ), it should be noted that in both cases SF levels were within the normal range, reaching supraphysiological levels (>20 μg/l) (35) in the group with normal cognitive function.…”
Section: Discussionsupporting
confidence: 54%
“…The superior schooling of Chilean women, as well as their prolonged interactions with family members, might stimulate cognitive function (28,29) . As in other studies, a lower risk of cognitive impairment was observed in those with higher levels of education (30)(31)(32) , which might be explained by greater cognitive reserves from superior cortical and neuronal synaptic capacities or improved compensation for deficiencies arising from other brain regions (33,34) . Although the difference in SF levels was statistically significant when comparing our participants with normal and impaired cognitive function (MMMSE plus PFAQ), it should be noted that in both cases SF levels were within the normal range, reaching supraphysiological levels (>20 μg/l) (35) in the group with normal cognitive function.…”
Section: Discussionsupporting
confidence: 54%
“…Results from previous studies have also found that those with less education were more likely to be cognitively impaired [32,33]. Low education was thought to be related to cognitive impairment because individuals with lower education may reach old age with less initial cognitive reserve, poorer physical health, unhealthier lifestyles [34,35], and a greater risk for cognitive decline and generally appear to be on an earlier aging trajectory relative to those with higher levels of education.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have reported a higher prevalence of CIND in rural populations, both in Western populations and in the Chinese population [15,[19][20][21]. Two studies from Spain reported that the prevalence of CIND was 23.3% in rural areas and 13.8 and 14.7% in urban areas [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from Spain reported that the prevalence of CIND was 23.3% in rural areas and 13.8 and 14.7% in urban areas [19,20]. The prevalence of CIND was 12.3% in rural populations from northern Portugal, with a rural/urban prevalence ratio of 1: 3 [21].…”
Section: Discussionmentioning
confidence: 99%